CO2 emissions from karst cascade hydropower reservoirs: mechanisms and reservoir effect. (12th March 2021) - Wang, Wanfa; Li, Si-Liang; Zhong, Jun; Wang, Lichun; Yang, Hong; Xiao, Huayun; Liu, Cong-Qiang
Abstract: Carbon dioxide (CO2 ) emissions from aquatic surface to the atmosphere has been recognized as a significant factor contributing to the global carbon budget and environmental change. The influence of river damming on the CO2 emissions from reservoirs remains poorly constrained. This is hypothetically due to the change of hydraulic retention time (HRT) and thermal stratification intensity of reservoirs (related to the normal water level, NWL). To test this hypothesis, we quantified CO2 fluxes and related parameters in eight karst reservoirs on the Wujiang River, Southwest China. Our results showed that there was a significant difference in the values of p CO2 (mean = 3205.7 μ atm, SD = 2183.4 μ atm) and δ 13 CCO2 (mean = −18.9‰, SD = 1.6‰) in the cascade reservoirs, suggesting that multiple processes regulate CO2 production. Moreover, the calculated CO2 fluxes showed obvious spatiotemporal variations, ranging from −9.0 to 2269.3 mmol m −2 d −1, with an average of 260.1 mmol m −2 d −1 . Interestingly, the CO2 flux and δ 13 CCO2 from reservoirs of this study and other reservoirs around the world had an exponential function with the reservoir effect index ( Ri, HRT/NWL), suggesting the viability of our hypothesis on reservoir CO2 emission. This empirical function will help to estimate CO2 emissions from global reservoirs and provide theoretical support for reservoir regulation to mitigate carbon emission.